2023
DOI: 10.3390/biology12060789
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Systemic Resistance in Hibiscus sabdariffa Linn. to Control Root Rot and Wilt Diseases Using Biotic and Abiotic Inducers

Abstract: The possibility of inducing systemic resistance in roselle against root rot and wilt diseases was investigated using biotic and abiotic inducers. The biotic inducers included three biocontrol agents (i.e., Bacillus subtilis, Gliocladium catenulatum, and Trichoderma asperellum) and two biofertilizers (i.e., microbein and mycorrhizeen), while the abiotic inducers included three chemical materials (i.e., ascorbic acid, potassium silicate, and salicylic acid). In addition, preliminary in vitro studies were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…However, pepper plants are susceptible to various diseases during their growth process due to climate change, pest invasion, and natural disasters. These diseases can reduce the yield and quality of pepper crops, causing serious economic losses to farmers [3,4]. Therefore, timely and accurate identification of pepper diseases is crucial for effective disease control and the sustainable development of the pepper industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, pepper plants are susceptible to various diseases during their growth process due to climate change, pest invasion, and natural disasters. These diseases can reduce the yield and quality of pepper crops, causing serious economic losses to farmers [3,4]. Therefore, timely and accurate identification of pepper diseases is crucial for effective disease control and the sustainable development of the pepper industry.…”
Section: Introductionmentioning
confidence: 99%
“…These cutting-edge methodologies provide a detailed understanding of the physiological and biochemical states of vegetation, enabling us to understand plant responses to various environmental conditions [2,3]. These tools not only improve the accuracy of traditional assessments but also open up new possible innovative approaches for monitoring plant health and managing agriculture [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This combination allows for more comprehensive analysis by combining biochemical and biophysical insights [31]. Such a multifaceted approach enhances the understanding of plant responses and interactions with their environment, aiding in more accurate and predictive modelling of plant physiology and agronomy by remote-sensing techniques [4][5][6]32].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have indicated the efficiency of potassium silicate in controlling fungal diseases. Among these reports, Ahmed et al, 2023 who found that the application of potassium silicate at a rate of 4 g/L was the most effective in decreasing the incidence of roselle root rot and wilt caused by M. phaseolina, F. solani, and F. oxysporum. Similarly, Whan et al (2016) found that spraying cotton with potassium silicate was effective against wilt disease caused by F. oxysporum f. sp.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%